Transesterification of diethyl oxalate with phenol using MoO3/SiO2 catalyst - Biradar, Ankush V.; Shubhangi B. Umbarkar; Dongare, Mohan K. (Applied Catalysis A-General, 2005)
Transesterification of diethyl oxalate (DEO) with phenol to form diphenyl oxalate (DPO) has been carried out in liquid phase using MoO3/ SiO2 solid acid catalyst with high conversion and 100% selectivity. A series Of MoO3/SiO2 catalysts with different Mo loadings (1-20 wt%) were prepared using sol-gel technique and characterized using X-ray diffraction analysis (XRD), BET specific surface area, temperature-programmed desorption (TPD) of ammonia, and FTIR spectroscopic analysis of adsorbed pyridine. XRD analysis revealed the amorphous nature of the catalyst up to 10 wt% MoO3 loading and the formation of crystalline α-MoO3 phase on amorphous silica support with higher MoO3 loading. BET surface area showed high surface area for catalysts prepared by sol-gel technique with lower MoO3 content; the surface area decreases with increasing MoO3 loading. Ammonia TPD shows much higher acid strength compared to the catalysts prepared by impregnation technique. Among the series of catalysts prepared, MoO3/SiO2 containing 1 wt% MoO3 was found to be the most active catalyst for transesterification reaction, with a maximum DEO conversion of 80.9 and 100% selectivity for DPO. The effects of reaction temperature and catalyst concentration on conversion and product selectivity have been investigated. © 2005 Elsevier B.V. All rights reserved.
Keywords: diethyl oxalate; diphenyl oxalate; MoO3/SiO2; sol-gel technique; transesterification

Tailor made ionic liquids: catalyst and media for organic transformations - Chandra, Prakash; Shinde, Sandip S.; Biradar, Ankush V. (Current Organic Chemistry, 2015)
Ionic liquids are considered as one of the safe, green and environmentally benign solvents/catalysts for many organic reactions. Particularly, imidazolium based ionic liquids attracted much attention in basic as well as applied research. The major role of these ionic liquids is the replacement of the existing corrosive solvents, which are largely used in most of the organic processes and make these processes more eco-friendly. Recent report reveals the importance of imidazolium based ionic liquids, supported on silica gel or polystyrene in catalysis. The solid supports have well versed properties such as easy anchoring of ionic liquid, chemically and mechanically very stable and inert in nature. These ionic liquids can be tailored either by covalent attachment or simple deposition of the ionic liquid on the surface of the support. Both approaches showed enhanced reactivity and selectivity for various reactions. In this review, we made an attempt to review the recent reports related to synthesis and applications of tailor made ionic liquids and their use as catalyst in Aldol, Friedel-Crafts alkylation, hydroformylation, nucleophilic substitution and biomass transformation reactions.
Keywords: Green solvent; heterogeneous catalyst; organic transformation; sustainable process; task-specific ionic liquids

Trifunctional mesoporous silica-based, highly active catalyst for one-pot, three-step cascade reactions - Biradar, Ankush V.; Patil, Vijayshinha S.; Chandra, Prakash; Doke, Dhananjay S.; Asefa, Tewodros (Chemical Communications, 2015)
We report the synthesis of a trifunctional catalyst containing amine, sulphonic acid and Pd nanoparticle catalytic groups anchored on the pore walls of SBA-15. The catalyst efficiently catalyzes one-pot three-step cascade reactions comprising deacetylation, Henry reaction and hydrogenation, giving up to similar to 100% conversion and 92% selectivity to the final product.